Synthesis and Detailed Physicochemical Characterization of Ti3C2Tx MXene via Optimized HF-Based Etching of Ti3AlC2 - Yegin, Mustafa; Celik, Aytekin; Halisdemir, Umay; Hasar, Halil (Springer, 2025)
This study systematically examines the effects of hydrofluoric acid (HF) concentration, etching temperature, and duration on the synthesis of Ti3C2Tx MXene from the Ti3AlC2 MAX phase. The results demonstrate that optimal etching conditions-30% HF at approximately 40 degrees C for 24-48 h-enable effective removal of the Al layer, controlled surface termination with -OH, -F, and -O groups, and preservation of structural integrity. Under these conditions, MXenes exhibit expanded interlayer spacing, improved exfoliation, and favorable morphological characteristics. However, excessively high HF concentrations (e.g., 40%) or prolonged etching times (beyond 48 h) lead to increased structural disorder, morphological degradation, and reduced thermal stability due to over-etching and defect formation. The study highlights the trade-offs between enhanced functionalization and material degradation, emphasizing the importance of fine-tuning synthesis parameters to balance surface chemistry and structural stability. These findings provide a practical framework for tailoring MXene properties for specific application requirements. The optimized synthesis protocol offers valuable guidance for producing high-quality MXenes for use in energy storage, catalysis, sensors, and other advanced material applications. [GRAPHICS] .
Keywords: Ti3C2Tx MXene; Hydrofluoric acid etching; Structural and morphological characterization; Surface functionalization